Bioética, eutanásia e suicídio assistido: comparação normativa, regulação e argumentos éticos em vários estados americanos e europeus - Ferreira, Luciano Maia Alves (2016)
Terminality of human life has always raised difficult questions in theory and in practice (if euthanasia is morally acceptable or not, what the Law says exactly in democratic States, what health professionals should do). There are several countries that have legalized euthanasia or assisted suicide. Others have legal provisions that decriminalize these practices. In Brazil the clinically anticipation of death is still seen as a legal and ethical problem, It can be regarded as illegal on the Criminal Code. In this work the aim was to expose, analyze and discus some essential aspects of voluntary euthanasia and medically assisted suicide comparing legal permission or non criminalization in states of European and American continents. The methodology used was the review of literature and critical analysis of concepts and arguments on the proposed themes and evaluations for professional conduct, protocols and laws. A documental study on euthanasia and assisted suicide in international and domestic regulations was also carried out in the countries studied. It was concluded that there are common aspects and particular aspects in each studied country and their legislations on the subject, including interpretation of human rights and bioethical principles, also common and particular points in each one. In Brazil this suggests we think about the presence or absence of these aspects, and how religious, legal and medical views support or reject the legalization of medical care to the anticipation of death.